Preoperative Simulation and Three-Dimensional Model for the Operative Treatment of Forearm Double Fracture: A Randomized Controlled Clinical Trial. Issue 6 (1st June 2022) - Zhang, Yin; Luo, Junchao; Cao, Li; Zhang, Shuijun; Tong, Yu; Bi, Qing; Zhang, Qiong
Abstract: Background: To assess the safety and efficacy of preoperative simulation and three-dimensional (3D) models in the treatment of ulnoradial diaphyses fracture. It was hypothesized that preoperative simulation and 3D printing might significantly shorten the mean operative time, intraoperative bleeding, and intraoperative fluoroscopy. Material and Methods: Forty patients with forearm double fracture were divided into 3D printing group and conventional surgery group. Preoperative simulation and 3D printing were performed on patients in the 3D printing group to examine implant reduction and placement as well as preoperative plate/screw size. The operation time, intraoperative bleeding, and frequency of fluoroscopies were recorded. Results: In the conventional surgery group, the operative time, intraoperative bleeding, and the frequency of fluoroscopy were 106.2 ± 15.92 min, 61.45 ± 11.33 ml and 5.65 ± 1.23 times, whereas in the 3D printing group, values of all the three parameters were better than those of the conventional surgery group (91.3 ± 14.85 min, 48.6 ± 10.39 ml and 3.85 ± 1.04 times, respectively). The forearm pronation and supination of the 3D printing group improved to 79.55 ± 5.12° and 76.80 ± 3.96°, respectively. In the conventional surgery group, patients also had significant improvement in these indicators, which improved to 78.60 ± 5.18° and 75.4 ± 5.30°. Conclusions: The results showed that preoperative simulation and 3D printing can enhance the safety as well as personalization of the surgical process during the treatment of forearm double fracture and therefore holds potential for future application in clinical practice. Trial registry: Name of the registry: This study was registered in the Chinese Clinical Trial Registry; Trial registration number: ChiCTR2100045790.